2010
DOI: 10.1007/s11606-010-1377-y
|View full text |Cite
|
Sign up to set email alerts
|

The Physician Clinical Support System-Buprenorphine (PCSS-B): a Novel Project to Expand/Improve Buprenorphine Treatment

Abstract: Opioid dependence is largely an undertreated medical condition in the United States. The introduction of buprenorphine has created the potential to expand access to and use of opioid agonist treatment in generalist settings. Physicians, however, often have limited training and experience providing this type of care. Some physicians believe having a mentoring relationship with an experienced provider during their initial introduction to the use of buprenorphine would ease implementation. Our goal was to describ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
48
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 61 publications
(48 citation statements)
references
References 31 publications
0
48
0
Order By: Relevance
“…However, these surveys examined buprenorphine prescribing generally and did not focus on unobserved versus observed induction differences or specifics. Similarly but not included in Table 2 as it was not a formal provider survey and instead a description of a mentoring program, the Egan et al report on PCSS-B reported buprenorphine induction dosing and timing issues as 2 of the 3 most frequent topics discussed between PCSS-B mentors and community providers (Egan et al, 2010). Based on a 2007 US state (Massachusetts) and a 2001 French regional sample, the practice of unobserved induction was common: the Massachusetts survey indicated that many physicians (43%) had adopted unobserved induction as regular practice (Walley et al, 2008); the French survey documented that 29% of pharmacy-based inductions were unobserved, and none were supervised by prescribing general practitioners or conducted in a medical office setting (Vignau et al, 2001).…”
Section: Provider and Practice Surveysmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these surveys examined buprenorphine prescribing generally and did not focus on unobserved versus observed induction differences or specifics. Similarly but not included in Table 2 as it was not a formal provider survey and instead a description of a mentoring program, the Egan et al report on PCSS-B reported buprenorphine induction dosing and timing issues as 2 of the 3 most frequent topics discussed between PCSS-B mentors and community providers (Egan et al, 2010). Based on a 2007 US state (Massachusetts) and a 2001 French regional sample, the practice of unobserved induction was common: the Massachusetts survey indicated that many physicians (43%) had adopted unobserved induction as regular practice (Walley et al, 2008); the French survey documented that 29% of pharmacy-based inductions were unobserved, and none were supervised by prescribing general practitioners or conducted in a medical office setting (Vignau et al, 2001).…”
Section: Provider and Practice Surveysmentioning
confidence: 99%
“…Primary care and general psychiatry settings typically do not require consecutive observed induction or consecutive daily visits to begin other chronic care treatments or when prescribing other controlled substances, although few other prescription medications have the potential of causing a syndrome such as acute precipitated opioid withdrawal. Induction issues were among the top issue for contacts to the Physician Clinical Support System for Buprenorphine (PCSS-B), a Substance Abuse and Mental Health Service Administration (SAMHSA)-sponsored national mentoring network for buprenorphine prescribers (Egan et al, 2010).…”
mentioning
confidence: 99%
“…6 Key differences include the small number of specialists who staff the teleECHO clinic and are able to offer guided practice and telementorship to numerous PCPs simultaneously. Also, the IAP ECHO program has thus far operated in NM and so has been implemented in one state rather than nationally.…”
Section: Introductionmentioning
confidence: 99%
“…1 As the United States faces increasing opioid-related overdose deaths and diagnoses of addiction, educational and mentoring activities of the PCSS-O are needed to educate health care providers to address opioid misuse and the use of medication treatment for opioid use disorder. 2,3 AMERSA and Substance Abuse journal (SAj) have previously published scholarship involving medication treatment for addictions in a special issue titled "Expanding Treatment for Opioid Use Disorder: The Role of Pharmacotherapies" and the role of prevention and engagement titled "From Risk Reduction to Implementation: A Special Issue on Addressing the Opioid Epidemic." 4,5 These 2 special issues generated many submissions for consideration of publication.…”
Section: Introductionmentioning
confidence: 99%